Evaluasi User Experience dengan mengadaptasi Mecue Questionnaire pada Aplikasi Reseller (Studi Kasus pada Aplikasi Evermos) - Ringgo Abriovenandita; Retno Indah Rokhmawati; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The shift in consumer spending to digital has also fueled the growth of online businesses, one of which is online resellers. It is clear from the Central Statistics Agency (BPS) that in 2020 there are 2.36 million companies engaged in e-commerce across the country. Of these, 1.77 million companies (75.15%) are located in Java. Evermos is a platform that connects brands and retailers to sell the best authentic Indonesian products. Therefore, the researchers evaluated the user experience aspects using the meCUE survey method on the Evermos app to identify which apps need improvement from a user experience perspective. The purpose of testing with the MeCUE questionnaire is to find out the advantages and disadvantages of the application under study. The MeCUE study is divided into 4 modules, each discussing product attributes (usefulness, usability, visual aesthetic, status, commitment), user sentiment (positive and negative), and consequences (product loyalty and intention to use), the last one concerns general evaluation product. The EVERMOS application evaluation results for all modules 1 to 4 of the EVERMOS application get the best usability rating or 80. The lowest test score is an indicator of negative emotions, which is 2.00. The results that can be used as a comparison when repairing applications are found in module IV, namely the Intention to Use indicator which gets a value of 3.00. This shows that this application is less attractive among users to use it every day.